Consumers Spiritual Rights In Indonesia: A Legal Study Of Sharia Fintech Implementation In The Consumers Protection Perspective - Irwan Sugiarto; Hari Sutra Disemadi (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
The Industrial Revolution 4.0 provided advances in financial services such as financial technology (fintech) innovations. The fintech concept that adapts to technological developments is expected to facilitate a more practical, secure, and modern financial transaction process, including digital-based financial services that are currently developing around the world. The implementation of fintech in Indonesia is divided into conventional fintech and sharia fintech which provides choices for the public in accessing financial services. The problem comes from the Muslim community who still do not believe in the implementation of the Islamic financial industry especially sharia fintech. The existence of skepticism from the community is the basis of this research. This research uses normative legal research methods to describe and explaining efforts to implement sharia fintech in protecting the consumers, especially the protection of “spiritual rights”. This protection can be pursued through the spread of sharia principles in which sharia fintech financing services do not contain usury, uncertainty (ghoror), speculation (masyir), hiding damage (tadlis), harming other parties (dharar), and avoiding illegal matters (haram). Then the implementation of sharia fintech in protecting the customer's spiritual rights can also be pursued by applying financing arrangements that have been regulated by applicable regulations and by Fatwa DSN-MUI, such as contract/akad al-bai', akad ijarah, akad mudharabah, akad musyarakah, akad wakalah bi al ujrah, and akad qardh.